A personagem Miguel e o contraste matutice X civilidade em O Coronel Sangrado de Inglês de Sousa - Dotto, Lucimeire Ferrari (2008)
The dissertation has as object of study the building of one of the key characters in the novel O Coronel Sangrado (1877) by the paraense writer Inglês de Sousa. It deals about Miguel Faria, a character who occupies a central place in this narrative, seen under a clear contrast established between matutice and civility, having as scenario the Amazon region. The analysis demonstrated, at first, through the relationship between the character and the city context (Belém; Óbidos) and the countryside (Paranameri), that she wore a social civilized mask, although she still kept her wild, rough nature, in order to survive in a society ruled by the duality between truth and disguise. Later, however, the analysis focused on the way the narrator s speech inscribes that of the character, under the Bakhtinian conception of novel as a quoted speech, revealed a character who, despite being built with a certain degree of dialogy thanks to the partnership with the narrative point of view through free indirect speech, ends up being conducted by the narrative voice, both acting as a refraction of authorial intention marked by the regional realistic obliquity. The result is a novel structured around two characters Miguel Faria and the one who gives title to the novel: the colonel Sangrado materializing the critical ideological standpoint of Inglês de Sousa about a region such as the Amazon dominated, on the one hand, by the power of colonelism and, on the other hand, by the idilic and exotic image of its wild nature